Comparative structural study of C60-lysine and C60-piperazine biocompatible aqueous solutions. Issue 1 (2nd January 2022) - Tomchuk, Alina A.; Voiteshenko, Ivan S.; Shershakova, Nadezhda N.; Andreev, Sergey M.; Turetskiy, Evgeniy A.; Khaitov, Musa R.; Ivankov, Oleksandr I.; Tropin, Timur V.; Tomchuk, Oleksandr V.; Avdeev, Mikhail V.
Abstract: Experimental scattering methods together with ab initio calculations were applied for the structural characterization of aggregates in aqueous solutions of fullerene C60 conjugates with amino acid lysine and piperazine. The obtained aggregate size distribution function, as well as fullerene to adduct molar ratio, were explained based on the analysis of intra- and intermolecular interactions. The analysis of the cytotoxic properties of both compounds confirmed their biocompatibility with no toxic effects.